Työkaluja hoivan poliittisen talouden feministiseen tarkasteluun - Kinnunen Heini; Lamberg Emma (Poliittisen talouden tutkimuksen seura ry., 2025)
Emma Dowling:The Care Crisis: What Caused It and How Can We End It? Verso: Lontoo, 256 sivua. 2021.
Nancy Folbre: The Rise and Decline of Patriarchal Systems: An Intersectional Political Economy. Verso: Lontoo, 320 sivua. 2021. (Kirja-arvio)